Neurological outcomes after on‐pump vs off‐pump CABG in patients with cerebrovascular disease. Issue 10 (3rd July 2019) - Dominici, Carmelo; Salsano, Antonio; Nenna, Antonio; Spadaccio, Cristiano; El‐Dean, Zein; Bashir, Mohamad; Mariscalco, Giovanni; Santini, Francesco; Chello, Massimo
Abstract: Background and aim of the study: The possible association of off‐pump coronary artery bypass graft (CABG) with reduced risk of postoperative stroke and enhanced benefits in high‐risk patients support the hypothesis that patients with a positive history of cerebrovascular disease would benefit from off‐pump coronary surgery. This study aims to investigate the impact of off‐pump CABG on the incidence of postoperative neurologic events in patients with a previous history of cerebrovascular disease. Methods: From January 2015 to September 2018, 414 patients underwent isolated CABG with a previous history of transient ischemic attack (TIA) or stroke: 295 patients had on‐pump CABG and 119 patients had off‐pump CABG. Neurological outcomes of interest are postoperative stroke (transient or permanent), delirium requiring pharmacological treatment or a combination of both, collectively defined "Major Adverse Neurological Events" (MANE). Propensity score (PS) adjusted analysis has been used for regression models. Results: Off‐pump CABG carried a lower incidence of postoperative stroke (3.4% vs 9.8%, P  = .046, PS‐adjusted odds ratio 0.34 with P  = .044). Postoperative delirium occurred more than twice as often in the on‐pump group (11.5% vs 4.2%, P  = .034, PS‐adjusted odds ratio 2.78 with P  = .043). The composite outcome of MANE occurred in 20.3% in the on‐pump group, and in 7.6% in the off‐pump group ( P  = .003). Other complications were similar between groups. Conclusions: In patients with a previous TIA or stroke, off‐pump CABG is associated with a reduced risk of stroke, delirium, and postoperative adverse neurological events, compared to on‐pump CABG. Patients with high neurological risk can potentially benefit from off‐pump CABG, due to an overall reduction of postoperative neurological complications.